Polyoxometalates: Polyoxometalates‐Modulated Reduced Graphene Oxide Flash Memory with Ambipolar Trapping as Bidirectional Artificial Synapse (Adv. Electron. Mater. 12/2018). (10th December 2018) - Chen, Xiaoli; Pan, Jingyi; Fu, Jingjing; Zhu, Xin; Zhang, Chen; Zhou, Li; Wang, Yan; Lv, Ziyu; Zhou, Ye; Han, Su‐Ting
Abstract : In article number1800444, Su‐Ting Han and co‐workers demonstrate a polyoxometalates (POMs)‐modulated reduced graphene oxide flash memory with ambipolar charge trapping properties. Synaptic functions with the benefit of ambipolar trapping are emulated at the device‐level. This concept constitutes an innovative paradigm of applications for integrating polyoxometalates composites and neuromorphic computing.